Psychological stress in inflammatory bowel disease: Psychoneuroimmunological insights into bidirectional gut–brain communications - Ge, Li; Liu, Shuman; Li, Sha; Yang, Jing; Hu, Guangran; Xu, Changqing; Song, Wengang (Frontiers in Immunology, 2022)
Inflammatory bowel disease (IBD), which includes Crohn’s disease and ulcerative colitis, is a chronic, relapsing immune-mediated disease. The accumulating evidence has confirmed that chronic psychological stress is considered a trigger of IBD deterioration and relapse. Meanwhile, studies have suggested that patients with IBD are at increased risk of depression and anxiety. However, the underlying mechanism of the crosstalk between psychological stress and IBD remains poorly understood. This review used a psychoneuroimmunology perspective to assess possible neuro-visceral integration, immune modulation, and crucial intestinal microbiome changes in IBD. Furthermore, bidirectionality of the brain-gut axis was emphasized in the context, indicating that IBD pathophysiology increases the inflammatory response in the central nervous system and further contributes to anxiety and depression-like behavioral comorbidities. This information will help accurately characterize the crosstalk between psychological stress and IBD disease activity. Additionally, clinical application of functional brain imaging and psychotherapy should be considered during the treatment and diagnosis of IBD with behavioral comorbidities. Here, this review elucidated the significance of more high-quality research combined with large clinical sample sizes and multiple diagnostic methods and psychotherapy, which is helpful to realize personalized therapeutic strategies for IBD patients based on stress relief.